Electroanalysis utilizing amperometric microdisk electrode arrays - Ordeig, O; del Campo, J; Munoz, F; Banks, C; Compton, R (2007)
This article reviews the literature dealing with electroanalytical applications of ultramicroelectrode arrays over the past twenty years. A brief theoretical description of the mass transport mode governing their behavior is given, after which the main fabrication methods are described. The applications described in the later sections of this review range from conventional electroanalysis, namely trace metal stripping methods, using mercury modified arrays to more recent advances in the field of biosensors (enzymatic, immunosensors and nucleic acid based ones). © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.